SERVICE QUALITY INFLUENCE ON CUSTOMER SATISFACTION LEVEL - Adi Kuswanto (Jurnal Ilmiah Ekonomi Bisnis, 2009)
This study is intended to analyze customer satisfaction by investigating factors which influence it, and proceed to investigate the influence of customer satisfaction toward word of mouth. The object of this research is Bank Danamon customers. Since satisfaction and word of mouth are subject to personally, questionnaire is used as research instrument. Questionnaire was distributed to 109 Bank Danamon customers. However, research variables can be categorized as dependent and independent variables. Independent variables are those which are used to measure service quality, such as tangibles (X1), reliability (X2), assurance (X3), and empathy (X4). Dependent variables are customer satisfaction and word of mouth. Result shows that only tangibles and empathy have positive effect on customer satisfaction. And also empirically prove that customer satisfaction influence word of mouth significantly.Keywords: tangibles, reliability, assurance, emphaty, satisfaction, word of mouth